Consumer Protection in the Malioboro Area, Yogyakarta City Against Culinary Stalls - Vicki Dwi Purnomo; Surodjo; Hasrul Buamona; Murdoko (PT FORMOSA CENDEKIA GLOBAL, 2023)
As the times progress, the more deviant crimes that occur in society, including crimes in the culinary business, it is also what makes society more sensitive to culinary business actors. The problems are (1) How is consumer protection related to food menu prices that are not listed by culinary business actors, (2) What are the legal consequences in the form of sanctions that occur to every culinary business actor if they do not include food menu prices. The method in this research is qualitative, juridical-empirical approach. research on how to protect consumers that consumers are very vulnerable to fraud perpetrated by business actors, the protection that consumers themselves expect from business actors is not in accordance with their expectations, there is no form of accountability given by business actors when consumers complain. Conclusion The application of consumer protection is in fact in the results of research facts that culinary business actors in Malioboro who still do not include the price of food menus do not receive any legal consequences at all, be it light sanctions or closures to revocation of business licenses or harsh sanctions in the form of administrative sanctions and criminal sanctions.